Effectiveness of the Alarm System Policy on Reducing Ambulance Response Time in Prehospital Emergency Patient Care - Chanchalotorn, Siwakorn; Ayurag, Tin; Suwansilisil, Supakorn; Siripakkaphant, Christsanutth; Ponsumritchok, Petnumnueng; Siritikul, Nattaphan; Waroonkun, Supanut; Prayunsangrussamee, Charupat; Tianwibool, Parinya (Journal of Health Science and Medical Research, 2023)
Objective: Reduction of ambulance response time leads to an increase in positive patient outcomes. Therefore, the aim of this study was to determine whether an accomplished response time within eight minutes could be increased after the introduction of an alarm system policy and to study if the mortality rate would be decreased after the introduction of alarm system policy. Material and Methods: An interrupted time series was conducted in the collection of code red patients between the following dates: 1st November 2015 and 31st October 2019. The data was collected from the medical records of Maharaj Nakorn, Chiang Mai Hospital. The collected data were separated into: the pre-protocol period (1st November 2015 to 31st October 2017) and the post-protocol period (1st November 2017 to 31st October 2019). Results: A total of 552 patients were included in the overall analysis. The success rates of response time within eight minutes of patients with code red in the pre-protocol period and post-protocol period were 64.62% and 73.11%, respectively. It was discovered that the success rate was significantly higher (adjusted odd ratio=1.627, 95% confidence interval: [1.017, 2.602]; p-value<0.05) in the post-protocol period versus the pre-protocol period. A decrease in the mortality rate in 24 hours and the mortality rate in the emergency room (ER) was observed in post-protocol period, from the interrupted time series model. However, no significant difference was evident through the process of statistical analysis. Conclusion: The implementation of the protocol could significantly reduce response time; thus, achieving the 8-minute goal. Hence, this protocol will be able to promote better emergency services in pre-hospital-based care.